Green Synthesis of Iron Nano Particles Using Mentha longifolia L. Extract - Faezeh Tavoosi; Reza Ghafarzadegan; Ahmad Mirshokraei; Reza Hajiaghaee (Institue of Medicinal Plants, ACECR, 2018)
Background: Zero- iron nanoparticles, due to their high degradation properties, cause the destruction of many pollutants. Among the methods for synthesizing iron nanoparticles, green synthesis using plant extracts is more beneficial for the synthesis of nanoparticles than other methods. Objective: In this research, zero iron nanoparticles are synthesized in a one-step process by using of Mentha longifolia L. extract, which includes phenolic compounds, from the reduction of iron (III) chloride salt. The purpose of this research is to synthesize and develop a green method for the preparation of zero iron nanoparticles. Methods: The extract was obtained by percolation method at room temperature and distilled water solvent. The extract was added to a FeCl3.6H2O iron solution of 0.01 M. The color change from yellow to dark brown indicates the formation of nanoparticles. Changing in pH and color of the solution after the start of the reaction were investigated and recorded. Specifications of the synthesized nanoparticles were analyzed using SEM (scanning electron microscopy), UV-vis and FTIR. Results: Iron nanoparticles were synthesized at 46°C, 87 min and the volume ratio of 0.01 M iron salts to the extract 5:1. In this condition, the nanoscale size was 30.44 nanometers, which was confirmed by the SEM image. Conclusion: The synthesis of zero-iron nanoparticles using Mentha longifolia L. extract is possible. The antioxidant compounds in the plant can reduce iron (III) and produce zero iron nanoparticles.